IMPACT OF EDUCATION REFORMS AND POLICIES ON THE QUALITY OF HIGHER EDUCATION IN PAKISTAN - Shafqat, Firdous; Kahanam, Afifa; Quraishi, Uzma (International Journal of Psychosocial Rehabilitation, 2020)
The study in hand is an analysis of educational reforms and policies and their impact on the quality in the higher education sector of Pakistan from 2005 to 2010. Three indicators of quality named performance indicator for programme evaluation, performance indicator for teacher evaluation and performance indicator for student evaluation were selected for the present study. The research was in quantitative paradigm and was designed as a causal comparative or ex-post facto research. The population of the study was all Private and Public Universities in the Province of Punjab and 600 respondents were selected randomly from the population. Undergraduate, postgraduate students and faculty members from different Public and Private Higher Education Institutions were selected for the research. The data were analyzed with the help of descriptive and inferential statistics. Finding and results were presented in the form of tables, graphs and graphic organizers. Overall, the results paint a very encouraging picture of the higher education sector of Pakistan, especially in public sector, as students seem to be highly satisfied with the key criterion of education quality identified by this study. Academic content and delivery scores, especially were high on student satisfaction scores, highlighting the quality of teachers and the content being delivered in these institutions. Graduating students reflected high aspirations and confidence in terms of the key skills they have acquired within their academic training. Research students similarly showed enthusiasm about the level of support provided to them and the facilities available for such work. Similarly, majority of the students reflected that the academic as well as administrative issues regarding different programs were being handled efficiently. No significant difference was recorded among educational quality of public and private sector.